A cosmopolitan duck moulting resort; Takslesluk Lake Alaska - King, James G (Wildfowl, 1973)
In the years (1963-65) Fish and Wildlife Service personnel caught and banded 4,483 ducks of eight species at Takslesluk Lake, Alaska. Recovery of 230 of these bands show a surprising dispersion through 40 degrees of latitude and 180 degrees of longitude or from North Carolina to Central Siberia.